Measurement of physical activity in older adult interventions: a systematic review. Issue 8 (14th August 2015) - Falck, Ryan S; McDonald, Samantha M; Beets, Michael W; Brazendale, Keith; Liu-Ambrose, Teresa
Abstract : Background: Interventions to promote physical activity (PA) among older adults can positively impact PA behaviour and other health outcomes. Measurement of PA must be valid and reliable; however, the degree to which studies employ valid and reliable measures of PA is unclear. The purpose of this systematic review was to evaluate the measurement tools used in interventions to increase PA among older adults (65+ years), including both self-report measures and objective measures. In addition, the implications of these different measurement tools on study results were evaluated and discussed. Methods: Four electronic research databases (MEDLINE, PsychINFO, Web of Science and EBSCO) were used to identify published intervention studies measuring the PA behaviour of adults over 65 years of age. Studies were eligible if: (1) PA was an outcome; (2) there was a comparison group and (3) the manuscript was published in English. Data describing measurement methods and properties were extracted and reviewed. Results: Of the 44 studies included in this systematic review, 32 used self-report measures, 9 used objective measures and 3 used both measures. 29% of studies used a PA measure that had neither established validity nor reliability, and only 63% of measures in the interventions had established both validity and reliability. Only 57% of measures had population-specific reliability and 66% had population-specific validity. Conclusions: A majority of intervention studies to help increase older adult PA used self-report measures, even though many have little evidence of validity and reliability. We recommend that future researchers utilise valid and reliable measures of PA with well-established evidence of psychometric properties such as hip-accelerometers and the Community Health Activities Model Program for Seniors (CHAMPS) Physical Activity Questionnaire for Older Adults.